2016
DOI: 10.1038/srep38516
|View full text |Cite
|
Sign up to set email alerts
|

Tunable electron heating induced giant magnetoresistance in the high mobility GaAs/AlGaAs 2D electron system

Abstract: Electron-heating induced by a tunable, supplementary dc-current (Idc) helps to vary the observed magnetoresistance in the high mobility GaAs/AlGaAs 2D electron system. The magnetoresistance at B = 0.3 T is shown to progressively change from positive to negative with increasing Idc, yielding negative giant-magnetoresistance at the lowest temperature and highest Idc. A two-term Drude model successfully fits the data at all Idc and T. The results indicate that carrier heating modifies a conductivity correction σ1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…The inset of Fig. 1(b) illustrates the configuration, which is the principal focus of this study, for the transport measurements carried out with a supplementary dc-current, I dc in order to examine the influence of the I dc 80 on both the non-oscillatory- and photo-excited oscillatory magnetoresistance in this system. Thus, the main panel of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inset of Fig. 1(b) illustrates the configuration, which is the principal focus of this study, for the transport measurements carried out with a supplementary dc-current, I dc in order to examine the influence of the I dc 80 on both the non-oscillatory- and photo-excited oscillatory magnetoresistance in this system. Thus, the main panel of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1(b) exhibits the R xx under constant photo-excitation of f  = 70.1  GHz at P  = 0.77  mW (solid lines) and in the dark (red-dashed-lines) for various values of I dc over the span 0 ≤  I dc  ≤ 20  μA . A detailed study of the influence of I dc on R xx under dark conditions appears elsewhere 80 . Figure 1(b) shows that the non-oscillatory magnetoresistance below B  = 0.05  T is uninfluenced by the I dc while the magnetoresistance for 0.05 ≤  B  ≤ 0.35  T changes from an overall positive magnetoresistance to an overall negative giant magnetoresistance with increasing I dc .…”
Section: Resultsmentioning
confidence: 99%
“…ZnO posses magnetic properties with influence of cobalt ions (Co), so ZnO:Co DMS can act as a ferromagnetic at room temperature [5]. The transition metal ions like Mn [6], Ni [7] and Co [8] were doped with ZnO thin films and were analyzed via RTFM previously. ZnO systems can be improved by doping cobalt due to its abundant electron-states and high solubility.…”
Section: Introductionmentioning
confidence: 99%
“…By now, a number of experimental and theoretical [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] studies have been carried out on the photo-excited transport in low dimensional systems. In addition to the photo-excited effects, the dark magneto-transport properties including positive magnetoresistance 51,52 , giant negative magnetoresistance [53][54][55][56][57][58][59][60][61] , and narrow negative magnetoresistance effect near zero field have also attracted recent experimental attention. So far as the larger negative giant magneto-resistance is concerned, recent studies have shown remarkable features such as size dependence, tunability with supplemental dc-current, and coexistence with-and separability from-radiation induced magnetoresistance oscillations [59][60][61][62][63][64][65] .…”
mentioning
confidence: 99%
“…In addition to the photo-excited effects, the dark magneto-transport properties including positive magnetoresistance 51,52 , giant negative magnetoresistance [53][54][55][56][57][58][59][60][61] , and narrow negative magnetoresistance effect near zero field have also attracted recent experimental attention. So far as the larger negative giant magneto-resistance is concerned, recent studies have shown remarkable features such as size dependence, tunability with supplemental dc-current, and coexistence with-and separability from-radiation induced magnetoresistance oscillations [59][60][61][62][63][64][65] . One emerging theory suggests that some of the observed features of the larger negative giant magnetoresistance effect could be a signature of a viscous electron liquid in the low magnetic field quasi ballistic transport regime.…”
mentioning
confidence: 99%